Sosialisasi Pendidikan (GERSANK) Gerakan Sayang Anak Sebagai Upaya Mempersiapkan Pendidikan Berkarakter dan Generasi Islami Bagi Masyarakat Desa Serba Aceh Tamiang - Fahriansyah Pasaribu; Nurmala; Riski Alfina; Sufriansyah; Nurul Hasanah (Fusion: Jurnal Pengabdian kepada Masyarakat, 2024)
In facing the complex challenges of educating the younger generation, "GERSANK" education (Children's Love Movement) has a vital role as an effort to prepare an Islamic generation and character education. In this context, value-based education becomes a strong foundation in overcoming the increasingly disturbing moral and national crisis. GERSANK does not just pursue academic achievement alone, but more than that, it emphasizes the formation of strong character and strengthening fundamental Islamic values. The method of implementing KKN service by STAI Jam'iyah Mahmudiyah Tanjung Pura students in Aceh Serba Tamiang regarding the socialization of "GERSANK" education as an effort to prepare for character education and an Islamic generation can be combined in one integrated plot. This research shows that overall, the "GERSANK" socialization program in Aceh Serba Tamiang is an initiative that has succeeded in exploring local potential and responding to educational challenges with holistic solutions. Through an inclusive and participatory approach, the KKN team from STAI Jam'iyah Mahmudiyah Tanjung Pura was able to design and implement a program that not only focused on academic aspects, but also on character building and Islamic values.